Understanding the impact of pediatric single large‐scale mtDNA deletion syndromes on caregivers: Burdens and challenges - McKenzie Chappell; Sumit Parikh; Elizabeth Reynolds (JIMD Reports, 2023)
Abstract Single large‐scale mitochondrial deletion syndromes (SLSMDS) are ultra‐rare, progressive multi‐system diseases that make children largely dependent on their caregivers for both medical and non‐medical needs. Yet, few studies have examined the burden felt among caregivers. As part of a larger research study, 42 caregivers of children with SLSMDS completed two surveys to assess caregiver burden. The Mitochondrial Care Network Patient Needs Survey (MCN‐PNS) is a novel assessment that examines the logistical, time, and financial costs experienced by caregivers of children with SLSMDS. The Zarit Burden Interview (ZBI‐22) is a validated assessment that examines caregivers’ psychological health. Results demonstrate the unique burden experienced by caregivers of children with SLSMDS. One notable finding was the high psychological burden. Nearly 90% of caregivers experience psychological burden, with 20% of caregivers at risk for anxiety and depression. Caregivers were primarily concerned about what the future held for their child. Additional burdens included the time required to coordinate the child's healthcare visits and financial strains. Caregivers reported minimal delays in establishing care with a mitochondrial care specialist and felt confident in their understanding of their child's disease and treatment(s). Overall, there is a need for expanded logistical, financial, and psychological support from mitochondrial disease centers and advocacy groups for caregivers of children with SLSMDS.